2018
DOI: 10.1021/acsanm.8b00421
|View full text |Cite
|
Sign up to set email alerts
|

Fermi-Level-Controlled Semiconducting-Separated Carbon Nanotube Films for Flexible Terahertz Imagers

Abstract: Carbon-nanotube-related (CNT-related) materials and structures are highly anticipated as potential building blocks for future flexible electronics and photonics. Despite the various promising applications of CNT-related materials, one obstacle is the lack of ability to globally control and tune the Fermi level of microscale-thick CNT films because these films require a certain thickness to maintain their free-standing shape and freely bendable flexibility. In this work, we report on Fermi-level-controlled flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 42 publications
0
43
0
4
Order By: Relevance
“…Wearable THz imaging technology has also gained increasing attention due to its superb performance in biochemical probing and damage detection. Recently, Suzuki et al reported a wearable carbon‐nanotube‐related THz imager based on chemical Fermi‐level‐controlled methods, which was sufficiently miniaturized to be attached at fingertips and delivered decent imaging performances.…”
Section: Applications Of Wearable Photodetector Systemsmentioning
confidence: 99%
“…Wearable THz imaging technology has also gained increasing attention due to its superb performance in biochemical probing and damage detection. Recently, Suzuki et al reported a wearable carbon‐nanotube‐related THz imager based on chemical Fermi‐level‐controlled methods, which was sufficiently miniaturized to be attached at fingertips and delivered decent imaging performances.…”
Section: Applications Of Wearable Photodetector Systemsmentioning
confidence: 99%
“…Contrary to significant potential and interest, the CNT film PTE photodetectors require further sensitivity improvement, which is attributed to their lower noise equivalent power (NEP) values [ 17–19 ] than those of the state‐of‐the‐art solid‐state detectors. [ 20,21 ] Thus, the underlying PTE conversion mechanism in CNT film photodetectors should be clarified to provide effective approaches for such aims.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4b shows the I–V characteristic acquired by the proposed photodetector with and without light irradiation, and the minimum NEP value under an uncooled nonvacuum condition reached 5.06 pWHz −1/2 . The thermal device design of the CNT film–metal parallel coupling [ 18 ] and PN junction formation via chemical carrier doping [ 19 ] were previously evaluated for sensitive operations. The obtained index here equals tenfold and sixfold sensitivity enhancement over these two types of photodetectors, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We previously utilized a Fermi‐level‐tuned p–n junction, CNT film based on the chemical doping of NaOH, and 15‐crown‐5‐ether solution to enhance the thermo‐power of CNT films. [ 36 ] However, this type of liquid‐based doping process is not suitable for sensor array fabrication in terms of miniaturization and uniformity. Therefore, we employed a dry process to fabricate a THz camera patch.…”
Section: Resultsmentioning
confidence: 99%
“…© 2021 Wiley-VCH GmbH thermo-power of CNT films. [36] However, this type of liquidbased doping process is not suitable for sensor array fabrication in terms of miniaturization and uniformity. Therefore, we employed a dry process to fabricate a THz camera patch.…”
Section: (3 Of 8)mentioning
confidence: 99%